Delivering the cell-impermeable DNA 'light-switching' Ru(ii) complexes preferentially into live-cell nucleus via an unprecedented ion-pairing method. Issue 7 (5th April 2016) - Zhu, Ben-Zhan; Chao, Xi-Juan; Huang, Chun-Hua; Li, Yan
Abstract : The cell-impermeable DNA 'light-switching' Ru(ii ) complexes can be delivered into live-cell nucleus by forming lipophilic Yin–Yang ion-pairs with hydrophobic weak-acids. Abstract : The dipyridophenazine (dppz) based ruthenium polypyridyl complexes are known as molecular 'light-switches' for DNA. This property is poised to serve in diagnostic and therapeutic applications, but the poor cellular uptake restricts their use in live cells. Herein, we show that the cellular uptake, and more interestingly and surprisingly, the nuclear uptake of cell-impermeable Ru(ii )–polypyridyl cationic complexes such as [Ru(bpy)2 (dppz)] 2+ were remarkably enhanced by three structurally unrelated biochemical agents (pentachlorophenol, carbonyl cyanide p -(trifluoromethoxy)phenylhydrazone and tolfenamic acid), by forming lipophilic and relatively stable ion-pair complexes, via a passive diffusion mechanism. Enantioselective imaging of live-cell nuclear DNA was observed between the two chiral forms of Ru(ii ) complexes. This represents the first report of an unprecedented new method for delivering the DNA 'light-switching' Ru(ii ) complexes into the nucleus of living cells via ion-pairing, which could serve as a promising general live-cell delivery method for other potentially bio-medically important but cell-impermeable metal complexes.